A Socially Non-inclusive Urban-Regional Development in Mexico: The Macrocephalic Growth of Mexico city in the Center Region (Global Journal of Human-Social Science, 2022)
Under the basic premise that an economy and its territory as a socioeconomic entity are inscribed into a nation s space Accordingly the concomitant sustainable handling of its natural resources and people s well-being depends on myriad factors among which stands out firstly the country s own socioeconomic dynamics and secondly but not least important the political capacity of the State s intervention into the economy as the foremost legal entity capable and social risponsible to advance the nation s economic strategy to promote simultaneously growth and social well-being into the nation Upon this framework the article aims at analyze the socioeconomic implications of the neoliberal economic strategy adopted by Mexico with particular reference to Mexico City CDMX vis- -vis Mexico s Center Region encompassing CDMX and neighboring states to demonstrate its failure and the compelling need to it towards a more balanced social-inclusive and sustainable one Time s horizon for the analysis ranges from 1980-2020e
Keywords: uneven development; unsubstainable and socially non-inclusive urban-regional imbalance